Sosialisasi Kegiatan Keselamatan Mahasiswa dalam Berkendaraan di Universitas Murni Teguh PSDKU Pematangsiantar - Henry Dunan Pardede; Calen Calen; Hengki Mangiring Parulian Simarmata; Erikson Damanik; Erwin Sirait (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Safety is the main priority when driving. The aim of this service is to provide awareness to students about the importance of driving safely on the road. The PKM activity method is carried out with seminars and direct questions and answers from speakers. The activity was attended by 30 students Murni Teguh University PSDKU Pematangsiantar. The activity was held in collaboration with the Campus with the Pematangsiantar Police and CV Teknik. As a result of PKM activities, students 100% understand the importance of safety when driving by adhering to good driving safety theory.